Better Coverage of the ACL Tibial Footprint and Less Injury to the Anterior Root of the Lateral Meniscus Using a Rounded-Rectangular Tibial Tunnel in ACL Reconstruction: A Cadaveric Study. Issue 3 (23rd March 2022) - Shao, Jiayi; Zhang, Jiahao; Ren, Shuang; Liu, Ping; Ma, Yong; Ao, Yingfang
Background: To better restore the anatomy of the native anterior cruciate ligament (ACL) attachment and fiber arrangement, researchers have developed techniques for changing the shape of the ACL bone tunnel during ACL reconstruction. Purpose: To compare the coverage of the ACL tibial footprint and influence on the anterior root of lateral meniscus (ARLM) between a rounded-rectangular tibial tunnel and a conventional round tibial tunnel for ACL reconstruction. Study Design: Controlled laboratory study. Methods: A total of 16 (8 matched-paired) fresh-frozen human cadaveric knees were distributed randomly into 2 groups: a rounded-rectangular tunnel (RRT) group and a round tunnel (RT) group. One of the knees from each pair was reamed with rounded-rectangular tibial tunnel, whereas the other was reamed with round tibial tunnel. Coverage of the ACL tibial footprint and areas of ARLM attachment before and after reaming were measured using 3-dimensional isotropic magnetic resonance imaging. Results: In the RRT group, the average percentage of ACL tibial footprint covered by the tunnel was 70.8% ± 2.5%, which was significantly higher than that in the RT group (48.2% ± 6.4%) ( P = .012). As for the ARLM attachment area, in the RT group, there was a significant decrease (22.5% ± 5.9%) in ARLM attachment area after tibial tunnel reaming compared with the intact state ( P < .001). Conversely, in the RRT group, the ARLM attachment area was not significantly affected by tibial tunnel reaming. Conclusion: Rounded-rectangular tibial tunnel was able to better cover the native ACL tibial footprint and significantly lower the risk of iatrogenic injury to the ARLM attachment than round tibial tunnel during ACL reconstruction.